2009
DOI: 10.1080/10926770903298006
|View full text |Cite
|
Sign up to set email alerts
|

Fear as a Mediator for the Relationship Between Child Sexual Abuse and Victimization of Relationship Violence

Abstract: Childhood sexual abuse (CSA) has been identified as a predictor for dating violence victimization; however, the mechanism for this relationship is unexplored. The current study examined whether fearful dating experiences may help explain the relationship between CSA and dating violence victimization. Participants (N =327 college women) completed self-report measures of CSA, fearful dating experiences, and dating violence. In a mediational model test, CSA was found to be positively associated with fear in dati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Although research on the influence of victimization on fear of crime is relatively broad, a significant position of this research has focused on property and violent crimes. However, recognizing the influence of juvenile sexual victimization on fear has been identified as a significant concern (Berliner & Saunders, 1996; Ulloa, Baerresen, & Hokoda, 2009). Research by Ulloa and colleagues (2009) on testing the effect of juvenile sexual victimization on relationship violence victimization during college discovered that previous fearful dating experiences played a significant mediating role for this relationship.…”
Section: Fear Of Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Although research on the influence of victimization on fear of crime is relatively broad, a significant position of this research has focused on property and violent crimes. However, recognizing the influence of juvenile sexual victimization on fear has been identified as a significant concern (Berliner & Saunders, 1996; Ulloa, Baerresen, & Hokoda, 2009). Research by Ulloa and colleagues (2009) on testing the effect of juvenile sexual victimization on relationship violence victimization during college discovered that previous fearful dating experiences played a significant mediating role for this relationship.…”
Section: Fear Of Crimementioning
confidence: 99%
“…However, recognizing the influence of juvenile sexual victimization on fear has been identified as a significant concern (Berliner & Saunders, 1996; Ulloa, Baerresen, & Hokoda, 2009). Research by Ulloa and colleagues (2009) on testing the effect of juvenile sexual victimization on relationship violence victimization during college discovered that previous fearful dating experiences played a significant mediating role for this relationship. However, Fisher and Sloan (2003) have highlighted that previous direct and indirect sexual victimization in a sample of college females was not a significant predictor of fear of being raped at night on campus.…”
Section: Fear Of Crimementioning
confidence: 99%
“…Wilson (29), after analysing many studies, connects the experience of sexual abuse in childhood with fears, anxiety, depression, insomnia, obesity, self-destructive behaviour, aggression, rage, hostility, poor self-confidence, use of drugs and suicide attempts in adulthood. It has also been shown that fear is very often the result of sexual abuse in childhood (4) and that sexually abused children are described by their teachers as anxious and shy in relation to their peers who were not abused (33). Fears and anxiety related to sexuality are especially frequent, which are not so expressed in those who have not been sexually abused (34).…”
Section: Psycho-pathological Consequencesmentioning
confidence: 99%
“…Buljan Flander and Ćosić (39) point out that sexually abused adolescents often show sexualized behaviour, a poor ability to differentiate between emotional and sexual relationships, they may become promiscuous, develop sexual identification disorders, or even show phobic avoidance of sexual stimulus, and in view of all this, are at risk of themselves becoming perpetrators of sexual crimes. Sexual abuse in childhood has been shown to be the strongest predictor of later risky sexual behaviour (40), but also a significant predictor of violence in interpersonal relationships (4).…”
Section: Problems In the Realm Of Sexualitymentioning
confidence: 99%
See 1 more Smart Citation